Management of Data Access with Quality of Service in PL-Grid Environment - Słota, Renata; Nikolow, Darin; Skałkowski, Kornel; Kitowski, Jacek (Computing and Informatics, 2012)
e-Science applications increasingly require both computational power and storage resources, currently supported with a certain level of quality. Since in the grid and cloud environments, where we can execute the e-Science applications, heterogeneity of storage systems is higher than that of computational power resources, optimization of data access defines one of challenging tasks nowadays. In this paper we present our approach to management of data access in the grid environment. The main issue is to organize data in such a way that users requirements in the form of QoS/SLA are met. For this purpose we make use of a storage monitoring system and a mass storage system model – CMSSM. The experiments are performed in the PL-Grid environment.